Hans Küng: Legacy and balance of a theological work - Oviedo Torró, Lluís (Razón y fe, 2021)
The death of Hans Küng offers a good opportunity to review not only his contributions, but an entire historical period, almost a golden era, of Central European theology. It is convenient to recognize, first, the stimuli that we have received from this theological program, which surprisingly connects with aspects of Pope Francis magisterium, before reviewing its limits to offer a balanced account. Küng invites a constant exercise of theological empathy; at the same time his work reminds us about the problems that raises every kind of liberal theology.